Hybrid peer-reviewed journals and publishing model: Bias or impartiality in editorial policy - Bachir Khezzani; Jadranka Nikolić; Mile Bosilkovski; Marija Dimzova; Ilia Tsachev; Magdalena Petrova Baymakova (Pharmacia)
In recent years, there has been a significant increase in scientific productivity—an increased number of published original articles, reviews, short communications, case reports, and letters to the editor. In this regard, there is a large number of peer-reviewed journals in all fields of scientific knowledge, including in the field of biomedical sciences. Many studies indicate the existence of so-called journal editorial board bias and acknowledge the difficulty of eliminating it. We present our brief opinion on an important topic such as how publishing policy in some peer-reviewed journals leads to feelings of bias and inequality among authors and how to address this.